Strategi Pengelolaan Sumber Daya Manusia Dalam Meningkatkan Kapabilitas Pegawai Pada Pemerintahan Kota Magelang - Utami, Siti Indah; Verawati, Dian Marlina (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2023)
This study aims to describe the management and development of human resources in Magelang City to improve the capabilities of employees in supporting public services. This study uses descriptive qualitative methods with data collection techniques literature study. The results of this study indicate that the government agencies of the Magelang City Government have developed resources to improve employee capabilities as a form of effort to provide excellent public services to the community through continuous education and training activities and the need for cooperation with their respective personnel and adjusted to each level. . Magelang City through the on the job method has developed human resources. In most cases, the training courses provided by the City of Magelang are in-service training for employees consisting of basic civil servant training courses and administrative and technical functional training.